2021
DOI: 10.1126/sciadv.abg5995
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy strategies for COVID-19: Current approaches and potential applications

Abstract: Coronavirus disease 2019 (COVID-19) continues to burden society worldwide. Despite most patients having a mild course, severe presentations have limited treatment options. COVID-19 manifestations extend beyond the lungs and may affect the cardiovascular, nervous, and other organ systems. Current treatments are nonspecific and do not address potential long-term consequences such as pulmonary fibrosis, demyelination, and ischemic organ damage. Cell therapies offer great potential in treating severe COVID-19 pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 152 publications
1
11
0
1
Order By: Relevance
“…Long-term consequences such as pulmonary fibrosis, demyelination, and ischemic organ damage are not addressed. Cell therapy is thought to offer great potential for treating severe COVID-19 symptoms due to its customizability and regenerative function [ 46 ]. Currently, preclinical and clinical cell therapy trials are under way regarding the immunomodulatory ability of mesenchymal stem cells for COVID-19-related lung injury treatment and the mitigation of hyperimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term consequences such as pulmonary fibrosis, demyelination, and ischemic organ damage are not addressed. Cell therapy is thought to offer great potential for treating severe COVID-19 symptoms due to its customizability and regenerative function [ 46 ]. Currently, preclinical and clinical cell therapy trials are under way regarding the immunomodulatory ability of mesenchymal stem cells for COVID-19-related lung injury treatment and the mitigation of hyperimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapies have demonstrated efficacy in treating conditions that were previously difficult to manage with conventional treatment modalities, including neurodegenerative, oncologic, and immunological disorders. Numerous cell therapy approaches have been studied such as induced pluripotent stem cells, mesenchymal stromal cells, and T cells [ 100 , 101 , 102 , 103 ]. In a variety of indications, safety and efficacy results of cell therapy have suggested that cell therapy may be exploited to treat COVID-19 patients [ 100 ].…”
Section: Available Therapeutics and Treatment Optionsmentioning
confidence: 99%
“…Numerous cell therapy approaches have been studied such as induced pluripotent stem cells, mesenchymal stromal cells, and T cells [ 100 , 101 , 102 , 103 ]. In a variety of indications, safety and efficacy results of cell therapy have suggested that cell therapy may be exploited to treat COVID-19 patients [ 100 ]. As of 1 January 2021, clinicaltrials.gov listed several cell therapy-based clinical trials targeting COVID-19 pathology.…”
Section: Available Therapeutics and Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV) [21] , and refractory viral infections in hematopoietic stem cell transplantation (HSCT) patients [22] , [23] . There is currently no gold-standard and definitive treatment for COVID-19, and considering its urgency, it has prompted scientists from all fields to investigate this problem, engendering a wide range of potential therapeutic options [24] ( Table 1 ). Advances in adoptive cell therapy have engendered an off-branch of cell therapy which, unlike conventional acellular vaccines, uses primed cells as vaccines, such as DC-based vaccines [25] .…”
Section: Immune Cell-based Therapies Against Sars-cov-2 Infectionmentioning
confidence: 99%